WACANA ASTRONOMIS DALAM TAFSIR BAHASA MADURA: Telaah TapseÍ€r Sorat Yaa-Siin (BhÄsa MadhurÄ) Karya Muhammad Irsyad - Fawaidur Ramdhani; Ahmad Qusyairi (STAI AL-ANWAR SARANG, 2020)
This article examines the scientific interpretations in the book Tapsèr Sorat Yaa-siin (Bhāsa Madhurā) by Muhammad Ershad. The presence of this Madurese interpretation has complemented a series of Nusantara’s Qur’anic exegesis which has a tendency towards scientific nuances. Therefore, it is important to study the Qur’anic exegesis of cultural observers as a form of safeguarding one of the treasures of Qur’anic exegesis works in Indonesia, especially those with local languages. This study will only focus on scientific interpretations that are astronomical. This study find out, the astronomical interpretations of the Tapsèr Sorat Yaa-siin (Bhāsa Madhurā) has four broad themes; the solar system, the sun's dimming process, the creation of the universe, and the solar and lunar eclipses. During the interpretation process, Muhammad Ershad adopted a lot of information contained in the scientific discipline of astronomy. Apart from that, he also displayed his own drawings to make the reader easier in understanding the explanation he provided.